Further survey of Australian ophthalmologist's diabetic retinopathy management: did practice adhere to National Health and Medical Research Council guidelines? - Yuen, J.; Clark, A.; Ng, Jonathon; Morlet, Nigel; Keeffe, J.; Taylor, H.; Preen, D. (Wiley-Blackwell Publishing Asia, 2010)
Background: To compare the self-reported management of diabetic retinopathy by Australian ophthalmologists with the 1997 National Health and Medical Research Council (NHMRC) guidelines. Methods: Self-reported cross-sectional survey of patterns of practice. Questionnaires were sent to all Australian ophthalmologists, comprising questions regarding professional details, diabetic retinopathy screening attitudes/practices and specific hypothetical management scenarios. Data were analysed using Chi-squared and adjusted logistic regression. Result: 480 of the 751 (64%) eligible Australian ophthalmologists participated. The majority (80%, n = 376) reported they consistently reviewed patient's glycaemic control, but only 55% and 41% regularly reviewed blood pressure and serum cholesterol control, respectively. Ophthalmologists generally adhered to NHMRC-recommended screening intervals, although only 38% agreed with the guidelines relating to screening of pre-pubertal diabetic patients. Fluorescein angiogram was used more than recommended, especially for mild non-proliferative diabetic retinopathy where 45% of respondents used this investigation. Practice duration >15 years was associated with more regular fluorescein angiogram use (OR = 3.74; 95% CI: 2.53-5.53, P < 0.001). In the clinical scenarios where clinically significant macular oedema was concurrently present with cataract or proliferative diabetic retinopathy, >26% referred to retinal subspecialists for management; 85% of the remaining ophthalmologists performed macular laser first. Respondents with practice duration >15 years were 7.8 times (P = 0.001) more likely to perform cataract surgery first. Conclusion: Diabetic retinopathy management guidelines were generally well followed by Australian ophthalmologists. However, areas of practice variation existed including frequent use of fluorescein angiogram. Significant proportion of practitioners referred diabetic patients to retinal subspecialists, who were more likely to adhere to guideline recommendations. Ophthalmologists with greater experience (>15 years) were more likely to employ practices differing from NHMRC recommendations. © 2010 The Authors. Journal compilation © 2010 Royal Australian and New Zealand College of Ophthalmologists.